PENERAPAN PEER TUTORING DILENGKAPI HANDOUT UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA - Purnama Dewi (Jurnal Pelita Pendidikan, 2020)
This research was conducted with the aim of knowing whether the implementation of peer tutoring equipped with handouts can improve student motivation and learning outcomes in class VII odd semester SMP Negeri-1 Lintongnihuta T.A. 2019/2020. This research is a Classroom Action Research. The subjects of this study were 1 class VII students, totaling 32 students. The data collection technique uses 20 questions of learning outcomes in the form of multiple choice questions and observation format sheets. The data analysis technique used is qualitative and quantitative data analysis. The results showed that peer tutoring equipped with handouts could improve: (1) student learning motivation, in cycle I, students with high motivation (10 people), medium motivation (5 people) and low motivation (17 people) were obtained, while in cycle II students with high motivation (18 people), medium motivation (14 people) and no more students who have low motivation; (2) Student learning outcomes in cognitive aspects. In the first cycle, the cognitive aspects of student learning completeness were 21.88% with an average value of 30.16, while in the second cycle it reached 93.75% with an average value of 87.97.